Distribution of Bed Nets with Malaria Cadres and Socialization on the Use and Maintenance of Insecticide-Treated Nets in the Community of Yongsu Spari Village, Ravenirara District, Jayapura Regency, 2025 - Jarona, Marlin M; Mehue, Bruce; Pamungkas, Akbar I; Purba, Lilys I.N.; Fien, Yeyen (Green Publisher Indonesia, 2026)
Malaria can be experienced by anyone, from children to adults. The cause of malaria is infection by Plasmodium parasites, transmitted through Anopheles mosquito bites. Malaria is an environment-based disease. Although many cases of malaria are mild and can resolve on their own, it remains a condition that bothers sufferers and can lead to complications. Therefore, malaria must be addressed as soon as possible. One factor contributing to stunting is recurrent malaria infection. Infectious diseases like malaria, accompanied by diarrhea and vomiting, can cause children to lose fluids and essential nutrients. To prevent stunting, programs are needed to increase public awareness of environmental health. This requires efforts to enhance public knowledge through community empowerment. The method implemented was the provision of malaria prevention cadre training using insecticide-treated nets because the role of malaria cadres is vital in breaking the chain of transmission. The program took place in May 2025 in Ravenirara District, Jayapura Regency. It was attended by 2 malaria cadres. To strengthen their role, education was delivered through counseling, training, and mentoring. Counseling aimed to increase and reinforce cadres' knowledge about malaria, training provided skills in using insecticide-treated nets, and mentoring equipped them to educate the community.